Generalized Lymphadenopathy due to Chronic Lymphocytic Leukemia (CLL) : 18F-FDG PET Imaging - Hidayat, Basuki; Hutomo, Febby; Yudistiro, Ryan; Mulyanto, Ivana D.; Budiawan, Hendra; Masjhur, Johan S. (Maranatha Christian University, 2016)
Lymphadenopaty is a common clinical finding with a broad differential diagnosis, withCarcinoma of Unknown Primary (CUP) as one of itâs most common causes. Flourine-18 fluoro-2 deoxy glucose (18F- FDG) positron emission tomography (PET) is a Nuclear Medicinescintigraphy procedure commonly used to localize suspected a primary lesion by depicting ametabolic status. However, in the expertise of 18F FDG PET study, clinical finding andepidemiologic data must be considered to get a better conclusion. We describe 18F-FDG PETstudy in the presence of generalized lymphadenopathy due to chronic lymphocytic leukemia(CLL), a rare disease which is initially suspected of having CUP.Keywords: 18F-FDG PET, lymphadenopathy, lymphoma, leukemia